DO ONLINE STUDENTS DREAM OF ELECTRIC TEACHERS? - Jason A. Scorza (Online Learning, 2019)
This paper represents a rough and ready attempt to describe an approach to online teaching that favors empathy over efficiency in the hope of achieving both.